Regional anaesthesia in patients on antithrombotic drugs: Joint ESAIC/ESRA guidelines. Issue 2 (February 2022) - Kietaibl, Sibylle; Ferrandis, Raquel; Godier, Anne; Llau, Juan; Lobo, Clara; Macfarlane, Alan JR; Schlimp, Christoph J.; Vandermeulen, Erik; Volk, Thomas; von Heymann, Christian; Wolmarans, Morné; Afshari, Arash
Abstract : BACKGROUND: Bleeding is a potential complication after neuraxial and peripheral nerve blocks. The risk is increased in patients on antiplatelet and anticoagulant drugs. This joint guideline from the European Society of Anaesthesiology and Intensive Care and the European Society of Regional Anaesthesia aims to provide an evidence-based set of recommendations and suggestions on how to reduce the risk of antithrombotic drug-induced haematoma formation related to the practice of regional anaesthesia and analgesia. DESIGN: A systematic literature search was performed, examining seven drug comparators and 10 types of clinical intervention with the outcome being peripheral and neuraxial haematoma. Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was used for assessing the methodological quality of the included studies and for formulating recommendations. A Delphi process was used to prepare a clinical practice guideline. RESULTS: Clinical studies were limited in number and quality and the certainty of evidence was assessed to be GRADE C throughout. Forty clinical practice statements were formulated. Using the Delphi-process, strong consensus (>90% agreement) was achieved in 57.5% of recommendations and consensus (75 to 90% agreement) in 42.5%. DISCUSSION: Specific time intervals should be observed concerning the adminstration of antithrombotic drugs both prior to, and after, neuraxial procedures or those peripheral nerve blocks with higher bleeding risk (deep, noncompressible). These time intervals vary according to the type and dose of anticoagulant drugs, renal function and whether a traumatic puncture has occured. Drug measurements may be used to guide certain time intervals, whilst specific reversal for vitamin K antagonists and dabigatran may also influence these. Ultrasound guidance, drug combinations and bleeding risk scores do not modify the time intervals. In peripheral nerve blocks with low bleeding risk (superficial, compressible), these time intervals do not apply. CONCLUSION: In patients taking antiplatelet or anticoagulant medications, practitioners must consider the bleeding risk both before and after nerve blockade and during insertion or removal of a catheter. Healthcare teams managing such patients must be aware of the risk and be competent in detecting and managing any possible haematomas. Abstract : Supplemental Digital Content is available in the text